Business linkage and performance of small and medium-sized enterprises: A case study of enterprises engaged in exporting agricultural products - Loan, Nguyen Thi; Xuan, Nguyen Thi Thanh; Nam, Nguyen Khanh (Nurture, 2023)
Purpose: Recently, Vietnam’s agricultural exports have been on a steady rise making a substantial contribution to the country’s economic development in the most challenging times. This study aims to analyze the determinants of business performance among agricultural exporters in the context of international economic integration. Design/Methodology/Approach: The data were obtained from 253 enterprises in Vietnam using a structured questionnaire. The data analysis was carried out using SPSS 20.0 and AMOS software for structural equation modeling method (SEM) analysis to find the cause-and-effect relationship between exogenous and endogenous variables. Findings: The research findings indicate that market factors have the most significant impact on business performance (BP) followed by linkages and networks, management capacity and human resources in enterprises. Additionally, the study examines the moderating role of gender and the management experience of business owners in the relationship between factors and business performance. Conclusion: The results show that there is a statistically significant relationship between the eight proposed factors that determine the business success of SMEs operating in the field of export agriculture. There is no significant difference between age, sex and education level in the impact of factors determining the business performance of SMEs exporting agricultural products in Vietnam. Meanwhile, management experience and the number of years of export have the effect of regulating the impact relationship in the model. Research Limitations and Implications: This study was conducted on a national scale but the number of units participating in the survey is not really representative mainly concentrated in the northern and central Vietnamese exporters. Meanwhile, the South has a large number of export SMEs, so the sample coverage is insufficient. Practical Implications: Research results provide insight for businesses, state management agencies, credit institutions and associations on policy-making and appropriate solutions to support and develop exporting SMEs and enhance the effectiveness of agricultural export activities in the future. Contribution to Literature: The study has an important contribution both in theory and practice when fully systematizing and logically interpreting the determinants of BP for SMEs exporting agricultural products in Vietnam. In terms of practice, the relationship has been explained and management implications have been proposed especially in demand research and market access, building linkages and cooperation mechanisms between parties to strengthen the power of exporting SMEs.